« Tuttor ch’eo dirò “gioi” ». La « joie » appellatif de la dame dans la lyrique romane médiévale - Federico Saviotti (Revue des Langues Romanes)
The presence–in a French rondeau transcribed in a recently-discovered Italian fragment–of the appellation formula “douce yoye”addressed to the lyrical I’s beloved inspires a reflexion about the use of the noun “joy” in French (joie), Occitan (joi, joia) and Italian (gioi, gioia) in reference to the lady sung in the Medieval Romance Lyric. The analysis of the occurrences in the Troubadours’, Trouveres’ and Italian poets’ corpora allows to formulated an hypothesis about the evolution of his poetic function: from a proper pseudonym to a generic expression whose success is witnessed by its persistence in nowadays common language.